FORMULASI SEDIAAN SPRAY HAND SANITIZER PERASAN KULIT NANAS (Ananas comosus L. Merr) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Escherichia coli SECARA IN VITRO - Slamet, Slamet; Budi Sungkawa, Hendra; Dea Sari, Khafifah (Jurnal Laboratorium Khatulistiwa, 2023)
Pineapple peel has flavonoid compounds that are disinfectant and very effective in inhibiting the growth of gram-positive and gram-negative bacteria. This is because flavonoids are polar so it is easier to penetrate the peptidoglycan layer. Pineapple peel has a high inhibitory power against Escherichia coli and Staphylococcus aureus bacteria. This study aims to determine the effect of pineapple peel (Ananas comosus L. Merr) hand sanitizer spray preparation in inhibiting the growth of Escherichia coli bacteria in vitro. The design of this research is experimental research. The method used was disc diffusion. The population in this study is pineapple peel juice. The sampling technique used was purposive sampling. Based on the results of the study of 6 concentrations of pineapple peel juice hand sanitizer, the lowest inhibition zone was 6 mm at a concentration of 50% and the highest at a concentration of 100%, namely a 10 mm inhibition zone. From the results of the organoleptical test examination of the pineapple peel juice hand sanitizer spray preparation, which is liquid, light yellow in color, slightly cloudy and has a distinctive smell of perfume. pH is 6 at 50% 60% 70% 80% concentration and 5 at 90% 100%. The irritation test obtained negative results so that the product is safe for use on the skin. Homogeneity test is not homogeneous. Based on the results of the examination, the results of the organoleptical test, pH test, and irritation test meet the requirements but the homogeneity test does not meet the requirements in the aesthetics of spray hand sanitizer products.